2016
DOI: 10.1002/jnr.23951
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, behavioral, and neural consequences of sex chromosome aneuploidy

Abstract: The X chromosome has played a critical role in the development of sexually selected characteristics for over 300 million years, and during that time it has accumulated a disproportionate number of genes concerned with mental functions. There are relatively specific effects of X-linked genes on social cognition, language, emotional regulation, visuospatial, and numerical skills. Many human X-linked genes outside the X-Y pairing pseudoautosomal regions escape X-inactivation. Dosage differences in the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 90 publications
3
36
0
1
Order By: Relevance
“…Considering the increased prevalence of (characteristics of) behavioral and neurodevelopmental disorders, such as ADHD, autism spectrum disorders, anxiety, and depression in the SCT population, more knowledge of developmental neurocognitive risk markers could lead to more timely, preventive support, hopefully reducing the risk for these behavioral and neurodevelopmental disorders in the future. In addition, the results of this review call for more studies on early neurocognitive vulnerabilities, which are expected based on the impact of the extra chromosome on the development of the brain . It is important to learn more about the involvement of genes on the sex chromosomes in order to identify how expression of these genes can lead to the behavioral phenotype of individuals with SCT and how different genes on different sex chromosomes can lead to the similarities and differences in the behavioral profile of children with XXX, XXY, and XYY.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increased prevalence of (characteristics of) behavioral and neurodevelopmental disorders, such as ADHD, autism spectrum disorders, anxiety, and depression in the SCT population, more knowledge of developmental neurocognitive risk markers could lead to more timely, preventive support, hopefully reducing the risk for these behavioral and neurodevelopmental disorders in the future. In addition, the results of this review call for more studies on early neurocognitive vulnerabilities, which are expected based on the impact of the extra chromosome on the development of the brain . It is important to learn more about the involvement of genes on the sex chromosomes in order to identify how expression of these genes can lead to the behavioral phenotype of individuals with SCT and how different genes on different sex chromosomes can lead to the similarities and differences in the behavioral profile of children with XXX, XXY, and XYY.…”
Section: Discussionmentioning
confidence: 99%
“…estrogen) and sex chromosomes (e.g. X chromosome aneuploidy) on early brain development and neurodevelopmental disorders such as ADHD 25,42,43 , suggesting that future efforts to comprehensively examine the role of the sex chromosomes and their downstream products in the male bias in ADHD may be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…and behaviour (such as risk of autism spectrum disorder and attention-deficit/ hyperactivity disorder) 91 , and there is significantly higher mortality from a wide range of diseases 92,93 . However, such individuals also have reduced or increased dosage for the ~20 protein-coding genes in the pseudoautosomal regions, and, while early work suggested that the Turner Syndrome phenotype cannot be fully explained by the lack of a second copy of PAR1 94 , specific MSY genes remain to be convincingly implicated.…”
Section: Y-chromosomal Aneuploidymentioning
confidence: 99%